2018
DOI: 10.15713/ins.jcri.234
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Porphyromonas gingivalis isolated from oral cavity in Indian population - A culture-based study

Abstract: Background: Among the many oral bacteria residing in the oral cavity, Porphyromonas gingivalis is known to be the major organism associated with periodontitis. Different methods have been used for identification. However, culture is the gold standard in identification. Culture helps in characterization of the physiologic characters, identification pathogenic traits, virulence factors, etc. Gene alterations can be studied better if the organism is cultivated in the laboratory. Aims and Objectives: The aims and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Rojas et al (2017) found a prevalence of 73.3% in adult patients with diagnosed periodontal disease. Ingalagi et al (2018) found a high prevalence in healthy adult patients, as well as patients with periodontal disease. The prevalence of P. gingivalis was high in the group of healthy patients with 179 subjects (89.5%) compared to 109 subjects (54.0%) in the group of patients with periodontal disease.…”
Section: Porphyromonas Gingivalismentioning
confidence: 95%
“…Rojas et al (2017) found a prevalence of 73.3% in adult patients with diagnosed periodontal disease. Ingalagi et al (2018) found a high prevalence in healthy adult patients, as well as patients with periodontal disease. The prevalence of P. gingivalis was high in the group of healthy patients with 179 subjects (89.5%) compared to 109 subjects (54.0%) in the group of patients with periodontal disease.…”
Section: Porphyromonas Gingivalismentioning
confidence: 95%